True versus False Transformation: A Discussion of the Obstacles to Authentic Decolonisation at South African Universities. Issue 1 (2nd January 2019) - Zwane, Duduzile
Abstract: South African tertiary institutions have supposedly been in a transitional state for decades. The country's universities profess the merits of the transformation occurring within their walls. Despite this purported embrace of decolonised scholarship, the reality is that there is great ambivalence towards it. The highly publicised reports of tensions and inequalities shatter the illusion of this intellectual utopia. Consequently, this article interrogates the major issues that are impeding this supposedly seamless transition to a decolonised higher education system. It presents the criticisms that are regularly raised by decolonisation advocates. Significantly, a notorious public dispute between two respected scholars is utilised as a case study. The incident illustrates institutional hypocrisy and validates the criticism levelled against South African universities. Essentially, the article's overarching objective is to highlight the discrepancy between the idyllic fantasy of a decolonised university and the reality being experienced by South African scholars.